Elite soccer athlete's sleep: A literature review - Silva, A. C.; Amaral, A. S.; Guerreiro, R.; Silva, A.; de Mello, M. T.; da Silva, S. G.; Rechenchosky, L.; Rinaldi, W. (Apunts Sports Medicine, 2021)
Sleep is important for athletes to recover from training and competition. However, there are no systematic reports on sleep patterns of elite soccer adult athletes. This article described the sleep pattern of elite soccer athletes and identified it is factors associated. We included only original articles, written in English, and with professional male soccer players aged over 18 years old competing in the first national division. On days without match and at a matchday, the mean of total sleep time, sleep onset latency, and sleep efficiency were less than the National Sleep Foundation's recommendation in almost all articles. Both local and match outcomes can affect the sleep pattern. So, elite soccer athletes are often unable to achieve sleep recommendations. Home matches, defeat, or a draw, as well as travels, are factors that negatively affect the quality and quantity of sleep of the athletes.